The Prevalence and Indications of Intravenous Rehydration Therapy in Hospital Settings: A Systematic Review - Julia Gawronska; Ai Koyanagi; Guillermo F. López Sánchez; Nicola Veronese; Petre Cristian Ilie; Anne Carrie; Lee Smith; Pinar Soysal (MDPI AG, 2022)
(1) Objective: We performed a systematic review to explore the prevalence of intravenous (IV) rehydration therapy in hospital settings, and we assessed it by patient groups and populations. (2) Methods: A systematic review of major databases and grey literature was undertaken from inception to 28 March 2022. Studies reporting prevalence of IV rehydration therapy in a hospital setting were identified. The data were synthesised in a narrative approach. (3) Results: Overall, 29 papers met the inclusion criteria. The prevalence of IV rehydration therapy in paediatric patients ranged from 4.5% (hospitalised with diarrhoea and dehydration) to 100% (admitted to the emergency department with mild to moderate dehydration caused by viral gastroenteritis), and in adults this ranged from 1.5% (had single substance ingestion of modafinil) to 100% (hospitalised with hypercalcemia). The most common indication for IV rehydration therapy in paediatric patients was dehydration due to fluid loss from the gastrointestinal tract. Other causes included malnutrition, neuromuscular disease, bronchiolitis, and influenza. In adults, indications for IV rehydration therapy were much more diverse: fever, diarrhoea, drug intoxication, hypercalcemia, cancer, and postural tachycardia syndrome; (4) Conclusions: This systematic review showed that IV rehydration therapy in paediatric patients is often used to treat dehydration and diarrhoea, while in adults it has a broader spectrum of use. While IV rehydration therapy is important in correcting fluid problems and electrolyte status, the maintenance fluid prescribing practices vary considerably, and guidelines are scarce.